2016
DOI: 10.1111/pops.12325
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Normative Versus Nonnormative Action: The Role of Implicit Theories

Abstract: The current research investigates what motivates people to engage in normative versus nonnormative action. Prior research has shown that different emotions lead to different types of action. We argue that these differing emotions are determined by a more basic characteristic, namely, implicit theories about whether groups and the world in general can change. We hypothesized that incremental theories (beliefs that groups/the world can change) would predict normative action, and entity theories (beliefs that gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 48 publications
3
55
2
1
Order By: Relevance
“…That said, in both national samples, the direction of the effects were always positive, demonstrating that the younger generation in both societies has less wishes and expectations for peace than the older generations. As for political ideology, in line with past studies (e.g., Shuman et al 2016), dovish political ideology predicted higher wishes and higher expectations for peace. Looking separately at each component of hope, results demonstrate that political doves from both communities have higher expectations for peace compared to political hawks.…”
Section: Resultssupporting
confidence: 87%
“…That said, in both national samples, the direction of the effects were always positive, demonstrating that the younger generation in both societies has less wishes and expectations for peace than the older generations. As for political ideology, in line with past studies (e.g., Shuman et al 2016), dovish political ideology predicted higher wishes and higher expectations for peace. Looking separately at each component of hope, results demonstrate that political doves from both communities have higher expectations for peace compared to political hawks.…”
Section: Resultssupporting
confidence: 87%
“…It worth noting that in parallel to ESIM, a large amount of social-psychological research mainly draws upon the social identity model of collective action (SIMCA; van Zomeren, Postmes, & Spears, 2008) and has explored diverse antecedents that may predict people's participation in different forms of collective action including protest violence. In particular, some of those studies have suggested that social beliefs about how fair or dangerous the world is (Gulevich, Sarieva, Nevruev, & Yagiyayev, 2017), and certain implicit theories about social change (Shuman, Cohen-Chen, Hirsch-Hoefler, & Halperin, 2016) may increase people's readiness and willingness to carry out violent actions during protests (e.g., throw stones or bottles, clashing with the police). In addition, researchers have also suggested that certain emotions (i.e., anger and contempt) are critical to predict people's intentions to carry out non-violent or violent actions respectively (see Becker, Tausch, & Wagner, 2011;Tausch et al, 2011).…”
Section: Violence During Social Mobilisation Processesmentioning
confidence: 99%
“…Occupy Wall Street , Occupy London , Geraçao à Rasca, 15-M indignados … Although protest was established long ago as one of the most prevalent forms of political participation, the number of street demonstrations during the last decade has risen remarkably ( Kriesi, 2016 ; Shuman et al, 2016 ). The 2008 financial crisis had great impact on collective action tendencies ( Likki, 2014 ; Klandermans and van Stekelenburg, 2016 ; Kriesi, 2016 ; Sabucedo et al, 2017a ) many of them being rooted in anti-system claims ( Hughes, 2011 ; Páez et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%